دور نظام المعلومات المحاسبي في فعالية المراجعة الداخلية بالمؤسسة- اتصالالت الجزائر - - هيمة, سليم; زايد, عبد الرؤوف; براح, عبد المطلب (University of eloued جامعة الوادي, 2017)
The study deals with the role of accounting information system in achieving the effectiveness of Internal Audit (Algeria Telecom Corporation in El Oued), and the problem of basic research represented in the role of accounting information system to achieve the effectiveness of internal Audit, where the need arose to the accounting information system in the field of Audit since ancient times, Without a kind of censorship it becomes difficult to protect the assets of the institution or rely on their records. So we will try to explain the concepts of accounting information system and internal Audit as well as analysis of the list of the questionnaire in the Third quarter to validate the assumptions due to its great importance, and for this purpose has been to use percentages and duplicates, The study to validate the assumptions and a number of the most important results: The effectiveness of the internal Audit of the institution Algeria Telecom Corporation in El Oued is measured by its ability to follow sound
مذكرة ماستر تدقيق محاسبي
Keywords: نظام المعلومات المحاسبي، المراجعة الداخلية ، الرقابة الداخلية